Evaluation of Production Cost Efficiency and Gross Profit at Nasi Kebuli Restaurant, Pangkalan Brandan - Puspita Dewi; Ratih Amelia (SEAN Institute, 2026)
This study examines production cost efficiency and gross profit at Rumah Makan Nasi Kebuli Pangkalan Brandan during the period of January to June 2025. The study is grounded in the importance of production cost control in culinary businesses to maintain profitability amid fluctuations in raw material prices and operating costs. A descriptive quantitative method was employed, while data were collected through observation, interviews, and documentation. The data were analyzed using indicators of production cost efficiency, gross profit, and gross profit margin, and were further supported by lean manufacturing analysis to identify waste in the production process. The findings indicate that production cost efficiency ranged from 40.13% to 44.44%, with an average of 41.78%, while the average gross profit margin reached 29.35%. Throughout the six-month period, revenue and gross profit showed an upward trend; however, this increase was not consistently followed by improved cost efficiency due to fluctuations in raw material prices and operating expenses. The lean manufacturing analysis also revealed several forms of waste, including overproduction, waiting time, transportation, inventory, motion, over processing, and defects. Therefore, the business needs to strengthen raw material cost control, improve production management, and implement 5S principles continuously to enhance efficiency and financial performance.